Othello in the Balkans: Performing Race Rhetoric on the Albanian Stage - Golemi, Marinela (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
This essay examines the racialized rhetoric in Fan Noli’s 1916 Othello translation and the racialized performance techniques employed in A.J. Ricko’s 1953 National Theatre of Albania production. Hoping to combat racial discrimination in Albania, Noli’s translation of Othello renders the Moor an exceptional Turk whose alienation in Venice was designed to mirror the Albanophobic experiences of Albanian immigrants. Moreover, the Albanian Othello can serve as a platform for addressing ethno-racial tensions between Albanians and Turks, northern and southern Albanians, and Albanians of color and white Albanians. Both Noli and Ricko believed there was an anti-racist power inherent within Shakespeare’s play. In the end, however, the race-based rhetoric in the Albanian language, the use of blackface make-up in performance, and the logic and rhetoric of Shakespeare’s play itself challenged these lofty goals for race-healing.